You can lead with change (collection) - Hrebiniak, Lawrence G.; Black, Stewart; Hrebiniak, Lawrence G.; Black, Stewart (FT Press Delivers, 2013)
A brand new collection of best practices for successfully driving change and executing on strategy ... 2 authoritative books, now in a convenient e-format, at a great price! 2 authoritative Books help you execute on strategy and overcome the barriers to organizational change Even the highest-value strategies and most well-intentioned changes won't work if people don't execute on them. But, all too often, strategies aren't executed, and organizations don't change. This unique 2 Book package reveals why, and helps you overcome the specific obstacles to execution and change in your organization. In Making Strategy Work, Second Edition, Lawrence G. Hrebiniak presents a start-to-finish roadmap for formulating strategies that can be executed, and then executing them thoroughly and well. Updated and expanded throughout, this Book reflects new research at Wharton and beyond, new cases and techniques, and extensive new input from managers solving execution-related problems. Hrebiniak addresses issues including organizational structure, incentives, controls, coordination, information sharing, change management, culture, power, influence, and project management. In an expanded applications section, he applies his model to a wide range of challenging, real-world situations. This edition presents deeper analysis of strategy execution in global environments, techniques for linking project management to strategy, and executing on strategy in service organizations. Next, in It Starts with One, Third Edition, J. Stewart Black targets the #1 reason organizations don't change: the individuals within them can't change, because powerful mental maps stand in their way. Black offers a powerful, start-to-finish strategy for helping people redraw those mental maps, unleashing their power to deliver superior, sustained strategic change. He systematically identifies three brain barriers to change: failure to see, move, and finish . Then, he offers powerful tools, strategies, and solutions for overcoming all three. This edition is extensively revised to offer new insights, examples, and case studies -- from Facebook and Google to AMC and Lenovo. It concludes with a new five-step framework for integrating the elements of effective change leadership in real-world environments. You'll see this framework put to work through an important new case study: Deseret News, the rare newspaper that has learned to thrive in the digital era. If you're tasked with driving change or execut ...